Political research methods and practical skills - Halperin, Sandra 1950-; Heath, Oliver 1970- (Oxford Univ. Press, 2012)
Literaturangaben
Angezeigt u.d.T.: Halperin, Sandra: Researching politics
Keywords: Politische Wissenschaft; Empirische Sozialforschung; Methodologie